Pembuatan Laporan Keuangan Sederhana Berbasis Android dan Cloud untuk Peningkatan Literasi Keuangan UMKM - Haq, Aqamal; Iwan Ekawanto; Sri Susilowati (PT. Cendekia Sapta Indonesia, 2025)
This community service program aimed to improve the financial literacy of MSMEs in West Jakarta through training on preparing simple financial reports using Android-based applications and Cloud technology. The program involved 30 MSMEs under the West Jakarta Chamber of Commerce, representing trade, culinary, and service sectors. The training method combined lectures, hands-on practice with Android accounting applications, and the use of Cloud platforms for financial data management. Evaluation was conducted using pre-tests and post-tests. The results showed significant improvement: understanding of the importance of financial reports increased from 30% to 85%, the use of Android applications for recording transactions rose from 10% to 90%, and familiarity with Cloud technology grew from 20% to 75%. More than 85% of participants also expressed confidence in preparing financial reports to support access to external financing. This program highlights the importance of digital technology adoption for MSMEs as a step toward professional and competitive financial management.